Role of Professional Values in the Quality of Professional Life of Nurses - Maasoumeh Barkhordari-Sharifabad; Motahareh Mahdavi (Hamadan University of Medical Sciences, 2023)
Background and Objective: Professional values can play an important role in the quality of the professional life of nurses by motivating them to deal with ethical issues and guiding the way they interact with patients and their colleagues. This study aimed to determine the role of professional values on the quality of professional life of nurses working in Ayatollah Khatami Hospital in Khatam City, Yazd, Iran, in 2021. Materials and Methods: In this descriptive-cross-sectional research, the study population and research sample were the same. Accordingly, 103 nurses working in Ayatollah Khatami Hospital affiliated with Shahid Sadoughi University of Medical Sciences, Yazd, central Iran, were included in the study by census method. The data collection tools were questionnaires of demographic information, professional quality of life, and Nurses Professional Values Scale-Revised. Data analysis was performed using descriptive and inferential statistics in SPSS (version 21). Results: The average score of professional values was 105.91±13.38. Among the dimensions of quality of professional life, the highest and lowest mean values were related to the burnout dimension (36.06±5.50) and the secondary traumatic stress dimension (21.30±3.46), respectively. There was an inverse and significant statistical relationship between secondary traumatic stress and professional values (r=-0.175, P=0.03). There was no significant relationship between the two dimensions of job burnout and compassion fatigue with professional values. The regression analysis showed that professional values can be considered a predictor of secondary traumatic stress. Conclusion: Based on the results, nurses who provided care based on professional values had a lower level of secondary traumatic stress. Therefore, nursing managers should strive to promote awareness of professional values and provide necessary working conditions to reduce secondary traumatic stress in nurses.